cooI
Answered

Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Simplify the expression:

Do not use any spaces.

5x−3x+2x−x


Sagot :

= (5x - 3x) + (2x - x)

= 2x + x

= 3x

Note: 1x is the same as ‘x’

1x = x